The mechanism and ligand effects of single atom rhodium supported on ZSM-5 for the selective oxidation of methane to methanol. Issue 20 (14th May 2020) - Bunting, Rhys J.; Thompson, Jillian; Hu, P.
Abstract : The mechanism and ligand effects for the partial oxidation of methane to methanol on single atom rhodium supported on ZSM-5 are investigated by DFT. Abstract : The mechanism for the partial oxidation of methane to methanol on single atom rhodium supported on ZSM-5 is investigated by DFT. The most favoured mechanism for methane activation is shown to be via oxidative addition at an undercoordinated rhodium metal centre and not through a typical metal oxo intermediate. The formation of a C–OH bond, and not methane activation, is found to be the rate determining step. CO coordinated to the rhodium centre is observed to strongly promote this bond formation. Water is required in the system to help prevent catalyst poisoning by CO, which greatly hinders the methane activation step, and to protonate an intermediate RhOOH species. These results suggest that more focus is required on methyl–oxygen bond formation and that exclusive consideration of methane activation will not completely explain some methane partial oxidation systems.